PENGGUNAAN MEDIA GAMBAR SERI UNTUK MENINGKATKAN KEMAMPUAN MENULIS PARAGRAF SEDERHANA - Elsa Eppa Denita; Ade Maftuh; Deni Chandra (STKIP Al Islam Tunas Bangsa dan HEPI, 2023)
This research is motivated by the lack of ability to write simple paragraphs in class III students at SDN Cikembang. This is because the learning media used by the teacher is less attractive. The purpose of this study is to describe lesson planning, implementation of learning, and improving the ability to write simple paragraphs using picture series as media. The research method used was the class action research method (CAR) with the research subjects being class III students at SDN Cikembang. Based on the results of research using picture series media to improve the ability to write simple paragraphs, it shows that the use of picture series media can improve students' ability to write simple paragraphs. this can be seen from the acquisition of student learning outcomes, the average value of students in cycle I is 77.23 and the average value of students in cycle II is 83.10. So the increase from cycle I to cycle II is 17.65%. This series of picture media is recommended for use in improving the ability to write simple paragraphs of students.